(untitled) (Research, Society and Development, 2020)
Ossifying fibroma is a type of fibro-bone lesion characterized by asymptomatic volumetric increase, of slow evolution, which can reach large dimensions resulting in facial asymmetry, causing tooth displacement and functional impairment of the stomatognathic system structures. The purpose of this article was to the clinical report a case of a female patient, seen at the University Clinic, with a complaint of a volumetric increase in the right mandibular region with an evolution of approximately 1 (one) year. Before the total excision of the lesion, an incisional biopsy was performed with the diagnosis of ossifying fibroma. Due to the proportions of the lesion, the patient presented dysphagia, which resulted in an anemic condition, requiring normalization of the condition prior to the total excision of the lesion. After 6 months of follow-up, the patient showed significant improvement in the shape and function of the operated region, in addition to the nutritional deficiency. The assessment of the patient’s nutritional status is extremely important, should not be neglected, since malnutrition is directly linked to the evolution of the disease, and interferes with postoperative recovery.